Relationship between Smartphone Addiction and Nomophobia, Anxiety, Self-Control in High School Students - Akyol Güner, Türkan; Demir, İsa (Addicta: The Turkish Journal on Addictions, 2021)
This cross-sectional descriptive study, conducted among 970 high school students, aimed to examine the effects of smartphone use on nomophobia, anxiety, and self-control on high school students. Data were collected with the Personal Information Form, the Smartphone Addiction Scale, the Nomophobia Scale, the Beck Anxiety Inventory, and the Brief Self-Control Scale. It was determined that the students’ smartphone addiction was above a moderate level and that smartphone addiction was found to bear an effect on nomophobia, self-control, and anxiety. Evidence-based interventions to minimize smartphone use should be planned and implemented, especially in adolescents, who are reported to be the group at highest risk in terms of addiction.
Keywords: Anxiety; nomophobia; self-control; smartphone addiction; student